COINAGE SYSTEM OF MANIPUR - Begum, Mk. Washima; Oinam, Subhaarati; Singh, S. Dharmen (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Coins have been an important source in the construction of a state’s history. Coins are very much connected with the monetary history of a state and it helps in understanding the economic condition of a country in terms of its production and trade. It also provides detailed information about the political expansion, trade and trade routes. Earlier the Manipuri society practiced barter system to fulfill their needs. All business was carried on by means of barter or exchange. We have not been able to find any conclusive proof regarding the use of coin during the early parts of B.C.E. During the historical period the Manipuri king issued coins in various metals such as gold, silver, copper, bell metal, and so on. The coin's face value appeared to be the same as its intrinsic value. The paper is to examine the historical development of coinage system and to assess their roles and contribution in state economy during the pre-colonial period of Manipur.